Is the Strengths and Difficulties Questionnaire with a Trauma Supplement a Valuable Tool in Screening Refugee Children for Mental Health Problems?. Issue 1 (5th February 2019) - Fängström, Karin; Dahlberg, Anton; Ådahl, Kajsa; Rask, Hanna; Salari, Raziye; Sarkadi, Anna; Durbeej, Natalie
Abstract: The high number of asylum seekers in Sweden has highlighted the need to develop and evaluate structured assessment tools for children. In this study, we aimed to explore the utility of the Strengths and Difficulties Questionnaire (SDQ) with a trauma supplement of six items for preschool children in routine care. Parents of two- to six-year-olds ( N = 61) were asked to complete the questionnaire during the routine health check-up offered to all refugees upon their arrival to Sweden. Focus-group interviews were conducted with the nurses who used the SDQ. The nurses found the SDQ valuable once they established a routine and felt that the SDQ contributed to a more structured and informative conversation about the child's mental health. The SDQ total difficulties showed good internal consistency (alpha = 0.82). A significant proportion of children scored above the clinical cut-off and SDQ scores correlated significantly with the number of post-traumatic stress disorder symptoms measured using the supplement (rho = 0.29). The findings suggest that the SDQ with the trauma supplement is a useful tool in this clinical setting.